Therapeutic potential of perivascular cells from human pluripotent stem cells. (31st January 2013) - Dar, Ayelet; Itskovitz‐Eldor, Joseph
Abstract: Vascularization of injured tissues or artificial grafts is a major challenge in tissue engineering, stimulating a continued search for alternative sources for vasculogenic cells and the development of therapeutic strategies. Human pluripotent stem cells (hPSCs), either embryonic or induced, offer a plentiful platform for the derivation of large numbers of vasculogenic cells, as required for clinical transplantations. Various protocols for generation of vasculogenic smooth muscle cells (SMCs) from hPSCs have been described with considerably different SMC derivatives. In addition, we recently identified hPSC‐derived pericytes, which are similar to their physiological counterparts, exhibiting unique features of blood vessel‐residing perivascular cells, as well as multipotent mesenchymal precursors with therapeutic angiogenic potential. In this review we refer to methodologies for the development of a variety of perivascular cells from hPSCs with respect to developmental induction, differentiation capabilities, potency and their dual function as mesenchymal precursors. The therapeutic effect of hPSC‐derived perivascular cells in experimental models of tissue engineering and regenerative medicine are described and compared to those of their native physiological counterparts. Copyright © 2013 John Wiley & Sons, Ltd.